Urban affinity and its associated traits: A global analysis of bats - Janis M. Wolf; Jonathan M. Jeschke; Christian C. Voigt; Yuval Itescu (Global Change Biology, 2022)
Urbanization is a major contributor to the loss of biodiversity. Its rapid progress is mostly at the expense of natural ecosystems and the species inhabiting them. While some species can adjust quickly and thrive in cities, many others cannot. To support biodiversity conservation and guide management decisions in urban areas, it is important to find robust methods to estimate the urban affinity of species (i.e. their tendency to live in urban areas) and understand how it is associated with their traits. Since previous studies mainly relied on discrete classifications of species' urban affinity, often involving inconsistent assessments or variable parameters, their results were difficult to compare. To address this issue, we developed and evaluated a set of continuous indices that quantify species' urban affinity based on publicly available occurrence data. We investigated the extent to which a species' position along the urban affinity gradient depends on the chosen index and how this choice affects inferences about the relationship between urban affinity and a set of morphological, sensory and functional traits. While these indices are applicable to a wide range of taxonomic groups, we examined their performance using a global set of 356 bat species. As bats vary in sensitivity to anthropogenic disturbances, they provide an interesting case study. We found that different types of indices resulted in different rankings of species on the urban affinity spectrum, but this had little effect on the association of traits with urban affinity. Our results suggest that bat species predisposed to urban life are characterized by low echolocation call frequencies, relatively long call durations, small body size and flexibility in the selection of the roost type. We conclude that simple indices are appropriate and practical, and propose to apply them to more taxa to improve our understanding of how urbanization favours or filters species with particular traits.